Kajian terhadap hidrogel berasaskan selulosa bakteria (BC) dan kesan penggabungannya dengan nanopartikel perak sebagai agen antibakteria - Maryam Mokhtarom,; Azwan Mat Lazim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research investigated the ability of bacterial cellulose (BC) based hydrogel incorporated with silver nanoparticles as antibacterial agent. Free radical polymerization has been used to synthesize the BC hydrogel. The silver nanoparticles was integrated and reduced using sodium boron hydrate as the reducing agent. The swelling capability of the hydrogel at different pH was also examined. The FTIR results showed that acrylic acid (AA) was successfully grafted to the bacterial cellulose networks. Other analyses such as swelling tests, antibacterial, Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) were also carried out to the hydrogel sample. The antibacterial tests found that hydrogel incorporated with silver nanoparticles was able to inhibit the bacterial growth.